Coexistence of aerobic vaginitis caused by Enterococcus faecalis and human papilloma virus (HPV) infection as a risk factor for the development of cervical intraepithelial lesions - Amna Baraković; Mahira Jahić; Anis Cerovac; Fatima Numanović (Medicinski glasnik, 2025)
Aim: To determine the prevalence of aerobic vaginitis (AV) caused by Enterococcus faecalis (E. faecalis) in human papilloma virus (HPV)-positive women with pathological Pap test and to determine the most prevalent HPV type associated with E. faecalis infection. Methods: This prospective study was conducted at the Gynaecology Centre "Dr. Mahira Jahić" Tuzla and Primary Health Care Centre Tešanj (Bosnia and Herzegovina) in the period between February 2023 and March 2024. The research included 200 women aged 25 to 50 years. The examined group consisted of 100 women with a pathological (examined group) and 100 with a normal (control group) Pap test result. Results: Pathological Pap smears were found in 60 (out of 100; 60 %) women in the examined group: cervical intraepithelial neoplasia (CIN) 1 and CIN 2 in two women, respectively, CIN 3 in seven, atypical squamous cells of undetermined significance (ASCUS) in 29 and atypical squamous cells-high-grade cannot be excluded (ASC-H) in two women. Overall (both groups) prevalence of E. faecalis was 25.5% (51women); in 45 (22.5%) women E. faecalis was the only bacterial isolate, of which 42 (21%) in the examined group and three (1.5%) in the control group. High-risk HPV types were found in 62 (out of 100; 62%) women with the pathological Pap smear test. The association of E. faecalis and high-risk HPV positive women was found in 35 (35%) cases (moderately positive correlation; r=0.198). Conclusion: E. faecalis is very common in HPV 16 and 18 positive women and may represent a risk factor in the development of cervical intraepithelial lesions.
Keywords: Atypical Squamous Cells of the Cervix; risk factors; Papanicolaou Test; Uterine Cervical Dysplasia